A case of Exophiala dermatitidis infection in a child after allogeneic stem cell transplantation: case report and literature review of paediatric cases. (26th June 2017) - Tanuskova, Dominika; Horakova, Julia; Buzassyova, Darina; Poczova, Miroslava; Bodova, Ivana; Svec, Peter; Chocholova, Alica; Adamcakova, Jaroslava; Sykora, Tomas; Pozdechova, Miroslava; Geczova, Lucia; Kolenova, Alexandra
Abstract : Introduction. Exophiala dermatitidis is a relatively common environmental black yeast with worldwide distribution and is a rare cause of fungal infection, mostly in patients with certain predisposing factors. Due to the rarity of the infection, little is known about the specific predisposing factors, way of infection or treatment. Case presentation. Here, we report what is to our knowledge the first case of E. dermatitidis infection in a child after allogeneic stem cell transplantation. We also review all paediatric cases reported in the literature since 1993. Conclusion. This is, to our knowledge, the first reported case of E. dermatitidis infection in a child after allogeneic stem cell transplantation. This report should increase the awareness of E. dermatitidis in immunocompromised paediatric patients, particularly after stem cell transplantation.